The impact of unified theory of acceptance and use of technology and social cognitive theory on accounting students' intentions to learn audit software - Yohanes Raja Oloan Hutapea; Heddry Purba; Mila Susanti (The Contrarian : Finance, Accounting, and Business Research, 2026)
The growing digitalization of auditing requires accounting students to develop competencies in audit software; however, technology-centered models alone may not fully explain their learning intentions. This study integrates the Unified Theory of Acceptance and Use of Technology (UTAUT) and Social Cognitive Theory (SCT) to examine the determinants of students’ intention to learn audit software, with emphasis on task-specific self-efficacy. Data were collected from 97 accounting students using purposive sampling and analyzed with SEM-PLS. The results show that social influence significantly affects behavioral intention, while performance expectancy, effort expectancy, and self-efficacy are not significant. These findings indicate that students’ intentions are driven more by academic environment and social pressure than by perceived usefulness, ease of use, or individual confidence. This study highlights the limitation of UTAUT in structured system contexts and emphasizes the importance of contextual psychological factors in audit education.